On the convergence of the discretized parallel chaotic waveform relaxation method - Yuan, Dongjin (Applied mathematics and computation, 2003)
In this paper we establish several algorithm of discretized parallel chaotic waveform relaxation methods for solving linear ordinary differential systems based on some given models. Under some different assumptions on the coefficient matrix A and its multisplittings we obtain corresponding sufficient conditions for convergence of the algorithms. Also a discussion on convergence speed comparison of synchronous and asynchronous algorithms is given.